KEPUASAN KONSUMEN PADA HYPERMARKET KOTA TANGERANG SELATAN - Herawati, Tuti (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
The purpose of this study was to determine the effect of service quality on Carrefour consumer satisfaction. The object of analysis in this study is Carrefour Pamulang. While the units of analysis are consumers who were found shopping at the time the study was conducted. The research method uses quantitative, descriptive and survey. The analytical method used is a simple linear regression analysis with 84 samples and the sampling technique used is accidental sampling and the determination of the number of samples using the Slovin formula. Furthermore, the study was tested with the stages of analysis that included a descriptive analysis of the questionnaire, a validity test, a reliability test, a classic assumption test, a linear regression test and a coefficient of determination test. Hypothesis test results show that service quality has a positive and significant effect on customer satisfaction with a regression coefficient of 0.435 and determination of 18.9%, while the remaining 81.1% is explained by other variables outside this study, for example location, price, promotion, image and others. This finding proves that consumer satisfaction can be explained by service quality. The better the services provided will increase customer satisfaction, thus loyalty will be born.